THE EFFECT OF IMPLEMENTING THE TEACHING LEARNING PROCESS, TEACHER PERSONALITY AND STUDENT INTEREST ON MATHEMATICAL LEARNING ACHIEVEMENT IN CLASS XI AT ADABIAH 2 PADANG HIGH SCHOOL - Jon Maizar, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
This study reveals how the influence of the Teaching and Learning Process, Teacher's Personality and the interest in learning simultaneously and partially towards Mathematics Learning Achievement of Class XI students using data collection methods in the form of questionnaires and the methods used are descriptive analysis and multiple regression analysis. This study chose the object of research to Adabiah 2 Padang High School Students and data collection was done with primary data and secondary data with the Proposal Random Sampling method that is each student taken randomly So that the sample of this study was 75 students, taking was done by questionnaire distribution method. The results of the study variable teaching and learning, teacher personality and student learning interest simultaneously have a positive and significant effect on student achievement in class XI at the Adabiah 2 School of Padang. Variables in teaching and learning partially have a positive but not significant effect on mathematics learning achievement of class XI, teacher personality variables have a negative but not significant effect on mathematics learning achievement of class XI, while learning interest variables have a positive and significant effect on class XI learning achievement at Adabiah 2 High School Padang. Processing data using multiple regression with SPSS version 21 for Windows.